2006
DOI: 10.1007/s10704-006-6579-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale damage during fracture in silica glass

Abstract: We report here atomic force microscopy experiments designed to uncover the nature of failure mechanisms occuring within the process zone at the tip of a crack propagating into a silica glass specimen under stress corrosion. The crack propagates through the growth and coalescence of nanoscale damage spots. This cavitation process is shown to be the key mechanism responsible for damage spreading within the process zone. The possible origin of the nucleation of cavities, as well as the implications on the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Although no clear signs of dislocation or shear band nucleation are observed, the initial mechanisms of cavity nucleation are consistent with other MD simulations and experimental studies of silica deformation. [30,46] Previous studies on small diameter nanowires (similar in size to those in our study) have determined that the mechanism of yielding by dislocation is absent, and demonstrated that the main mechanical instability is a disorder-order transformation, resulting in the reduction in size of the nanowire neck until single atom chains emerge. [24,47] We proceed with analysis of the silica meshes, as shown in Figure 5, which shows the equivalent von Mises stress field at the maximum stress.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Although no clear signs of dislocation or shear band nucleation are observed, the initial mechanisms of cavity nucleation are consistent with other MD simulations and experimental studies of silica deformation. [30,46] Previous studies on small diameter nanowires (similar in size to those in our study) have determined that the mechanism of yielding by dislocation is absent, and demonstrated that the main mechanical instability is a disorder-order transformation, resulting in the reduction in size of the nanowire neck until single atom chains emerge. [24,47] We proceed with analysis of the silica meshes, as shown in Figure 5, which shows the equivalent von Mises stress field at the maximum stress.…”
Section: Resultssupporting
confidence: 72%
“…The fracture toughness of bulk vitreous silica was determined to be approximately 0.8 MPa m 1/2 . [29] The failure mechanisms occurring within the process zone at the crack tip in amorphous silica glass were studied by Bonamy et al [30] By implementing AFM experiments and MD simulations, the authors found that nucleation and growth of cavities are the dominant mechanism for failure within the process zone.…”
Section: Introductionmentioning
confidence: 99%
“…The same water weakening mechanism is known to be responsible for high rates of subcritical crack growth in siliceous minerals and glasses (Lawn, 1993). Recent studies suggest that even in the brittle, subcritical fracture of siliceous glass at room temperature there is a plastic process zone affected by water (Bonamy et al, 2006). A suggested mechanism applicable to salts (Skvortsova, 2004) and other minerals (Traskin, 2009;Traskin et al, 1998) is the so-called Rehbinder effect (Rehbinder and Shchukin, 1972).…”
Section: -1-1-1 Plasticity: Naclmentioning
confidence: 99%
“…the scale between the size of a silica tetrahedron and on the order of 10-100 nm [165][166][167][168] depending on the chemical composition of the glass) of the glasses dictates stress corrosion cracking in Region I. Methods that highlight mesoscopic features, such as the DP Total , may be beneficial in the study of β c .…”
Section: Change In the V Versus K I In Region I As A Functionmentioning
confidence: 99%